Orthodontic force regulates metalloproteinase-3 promoter in osteoblasts and transgenic mouse models - Li-Fang Hsu; Bei-En Chang; Kuo-Jung Tseng; Chih-Ching Liao; Shu-Chun Tsai; Hsuan-Yi Hsiao; Sheng-Chin Lin; Pei-Wen Liao; Yi-Jane Chen; Chung-Chen Jane Yao (Elsevier, 2022)
Background/purpose: Previously we demonstrated up-regulation of matrix metalloproteinase-3 (MMP-3) in human osteoblasts under compression and in bony specimens of experimental orthodontic tooth movement (OTM). Here, we studied the temporal characteristics of compression stimulation in human and mouse osteoblast cell lines, and generated a transgenic mouse model for assessing the MMP-3 expression during OTM. Materials and methods: We investigated MMP-3 expressions in human and murine osteoblasts through RT-PCR and luciferase assay, after compressive force loading. Inhibitors were added to identify the possible mechanisms for signal transduction. A human MMP-3 promoter was isolated, cloned and transfected to generate a transgenic mouse with a green fluorescent protein reporter. OTM was then initiated to observe the location and time course of transcriptional regulation of MMP-3 signals. Results: We found changes in the transcription of MMP-3 in response to mechanical force applied to both human and mouse osteoblast cell lines, suggesting that the response is positive across species. Cloned human MMP-3 promoter may cause the response of luciferase to 1% compression. Moreover, p38 inhibitor exerted a down-regulatory effect on MMP-3 promoter expression, although the inhibitory effect didn't reach a significant level. In the transgenic mouse OTM model, we again found increased expression of MMP-3 in response to mechanical force loading around the periodontal ligament. Conclusion: Mechanical force can stimulate MMP-3 expression, possibly through the p38 MAPK pathway, with its strongest signal occurring at 24 h. The mechanical responsiveness in MMP-3 promoter regions can be observed in both humans and rodents in vitro and in vivo.